THE REALIZATION OF â€œCORPORATE SOCIAL RESPONSIBILITY PROGRAMSâ€ AS A PART OF GCG IN INDONESIAN STATE-OWNED ENTERPRISES (Case Study of PERUM Jasa Tirta I in Malang Regency) - Sulasmiyati, Sri (Profit: Jurnal Adminsitrasi Bisnis, 2017)
â€œCorporate governance is as a set of rules that define the relationship between shareholders which is consists of managers, creditors, the government, employees and other internal and external stakeholder in respect to their rights and responsibilitiesâ€.One of the principles of GCG is Responsibility, which is related to a program, it called CSR(CSR). State-owned enterprises (SOE) as a corporate which is owned by the government, must apply its principles. The implementation of CSRâ€™s programs is a one way that could increase GCG condition. The regulation for CSR implementation of SOE in Indonesia has been stated by the government through Ministerial Decrees of BUMN. This research aims to find out how the realization of CSR programs on Perum Jasa Tirta I whether it is same as the governmentâ€™s rule. The research finding that the realizations of PKBL on the Perum Jasa Tirta 1 has been well implemented, annually funds are budgeted realized as much as nearly maximize and distributed effectively.Â Â